Fetal Autopsy—A Game Changer! - Elayedatt, Rinshi Abid; Krishnan, Vivek; Chandraprabha, Vidya (Journal of Fetal Medicine, 2023)
Fetal autopsy is one of the most useful investigations that can change or significantly add to the clinical diagnosis despite a prenatal ultrasonographic diagnosis of a fetal abnormality. It is often required to determine the cause of intrauterine death or miscarriages, provide recurrence risk, and is known to alter the final diagnosis and genetic counseling in nearly half of the cases. This article reviews the role of fetal autopsy and discusses its contributory role in confirming the diagnosis and its usefulness in the genetic counseling of cases with risk of recurrence in future pregnancies.
Keywords: fetal autopsy; perinatal pathology; perinatal autopsy; prenatal ultrasound; fetal anomalies